Improving Photosynthetic Capacity, Alleviating Photosynthetic Inhibition and Oxidative Stress Under Low Temperature Stress With Exogenous Hydrogen Sulfide in Blueberry Seedlings - Tang, Xuedong; An, Baiyi; Cao, Dongmo; Xu, Ru; Wang, Siyu; Zhang, Zhidong; Liu, Xiaojia; Sun, Xiaogang (Frontiers in Plant Science, 2020)
In this study, we investigated the mechanism of photosynthesis and physiological function of blueberry leaves under low temperature stress (4–6°C) by exogenous hydrogen sulfide (H2S) by spraying leaves with 0.5 mmol•L-1 NaHS (H2S donor) and 200 μmol•L-1 hypotaurine (HT, H2S scavenger). The results showed that chlorophyll and carotenoid content in blueberry leaves decreased under low temperature stress, and the photochemical activities of photosystem II (PSII) and photosystem I (PSI) were also inhibited. The electron transfer process from QA to QB on the PSII acceptor side was sensitive to low temperature. Low temperature stress can reduce photosynthetic carbon assimilation capacity by inhibiting stomatal conductance (Gs) of blueberry leaves, and non-stomatal factors also play a limiting role at the 5th day of low temperature stress. Low temperature stress leads to the accumulation of Pro and H2O2 in blueberry leaves and increases membrane peroxidation. Spraying leaves with NaHS, a donor of exogenous H2S, could alleviate the degradation of chlorophyll and carotenoids in blueberry leaves caused by low temperature and reduce the photoinhibition of PSII and PSI. The main reason for the enhancement of photochemical activity of PSII was that exogenous H2S promoted the electron transfer from QA to QB on PSII acceptor side of blueberry leaves under low temperature stress. Exogenous H2S increased Gs and carboxylation efficiency (CE) of blueberry leaves under low temperature stress, thus ensuring normal photosynthesis. In addition, it promoted the accumulation of osmotic regulator proline under low temperature stress and significantly alleviated membrane peroxidation in blueberry leaves. Exogenous NaHS also induced a slight increase in H2O2 content under low temperature stress, which may be an important secondary signaling molecule in low temperature response of blueberry leaves regulated by exogenous H2S. H2S scavengers (HT) aggravated photoinhibition and the degree of oxidative damage under low temperature stress. Improving photosynthetic capacity as well as alleviating photosynthetic inhibition and oxidative stress with exogenous H2S is possible in blueberry seedlings under low temperature stress.